Plant genotype and seasonality drive fine changes in olive root microbiota - Matteo Chialva; Silvia De Rose; Mara Novero; Luisa Lanfranco; Paola Bonfante (Current Plant Biology, 2021)
Due to global warming, the cultivation range of many crops is extending at higher altitudes and latitudes exposing plants to new climatic and environmental conditions, as early spring frosts. To face these issues in a sustainable agriculture context, new innovative technologies, as the use of biostimulants and the manipulation of plant microbiota, are emerging. Here, we focused on anarea of Northern Italy in which olive tree cultivation, a traditionally and economically-relevant item of Mediterranean agriculture, is rapidly extending to inland cold-temperate areas. We conducted an assessment of the prokariotic and fungal microbiota present in the root endosphere of a cold-hardy and a cold-susceptible Italian olive cultivar (Leccino and Frantoio, respectively) along spring and winter seasons. Microbiota assembly and diversity analysis revealed that the root microbiotas of more than 20 years-old plants were highly stable with few variations occurring across seasons and genotypes. Notably, we detected fine seasonal-dependent community adjustments in the cold-susceptible genotype, which involved beneficial microbes and pathogens. Moreover, different patterns of abundance were found for arbuscular mycorrhizal fungi and their endobacteria revealing the presence of intimate tripartite interactions. Overall, the results suggest that a healthy and highly stable root microbiota could provide a useful tool to help olive trees to face new environmental issues as those related to climate change.